Penegakan Hukum Pidana Terhadap Praktek Perjudian Dalam Ritual Tiwah di Kabupaten Kapuas - Achmadi Achmadi (Anterior Jurnal, 2016)
The Indonesian legal system until now still in effect is a legal system which still facing to the Netherlands the legal system continental Europe or a system of civil law. Evidence of the legal system this is a book the act of criminal law and the book the act of civil law that until recently was are still remain in effect. In spite of in the legal system positive written above system does law another which is regarded remain in effect is a system adat law. Adat law is those laws life and developing in the community. Research non doctrinal in the form of studies empirical aimed to locate theories on the process the occurrence and on the process it work law in the of community or socio-legal research that is analyzed on law enforcement criminal in the sight of law enforcement (as the police) for finding and the process of the investigation and policies the government in support eradication gambling in Kuala Kapuas regency for the Dayaks of ngaju who performs gambling in any nuptial rites tiwah. The concept of gambling in the implementation of the rites tiwah held outside an arrangement of event rites tiwah in the view of unscrupulous law enforcement (police) in the timpah percent the concept is pure gambling, which reversed these activities there are profits gained, to enrich themselves, gambling and the concept of these is gambling that is well planned and organized.